PHYSIOLOGICAL ANALYSES OF AN OVER-EXPRESSING CYTOKININ METABOLIC GENE GmIPT10 UNDER NORMAL AND DROUGHT CONDITIONS - Hai, Nguyen Ngoc; Van Thien, Nguyen Duc; Lan Xuan, Hoang Thi; Thao, Nguyen Phuong (Vietnam Journal of Biotechnology, 2018)
Cytokinin (CK) is an important phytohormone, which not only plays significant role in plant development but also involves in mediating plant stress tolerance. Previous studies showed that the drought tolerance can be improved by stress-inducible overexpression of adenine isopentenyl transferase (IPT), which is a critical enzyme in CKs biosynthesis. To study the role of soybean GmIPT10 in regulating plant tolerance, we successfully generated GmIPT10-overexpressing transgenic soybean plants and screened a line carrying homozygous, single copy of transgene. Analyzing several physiological traits of this line demonstrated that it possessed stress tolerance characteristics, including increased primary root and shoot lengths, better production of shoot biomass, higher number of trifoliate leaves, and higher survival rate than the non-transgenic plants under drought condition. The net house experiments also showed that the GmIPT10-overexpressing transgenic soybean had a greater relative water content compared to the control genotype under applied drought condition. Therefore, this report indicated that plant drought tolerance might be enhanced via regulating expression of GmIPT10.